The Impact of Digital Payment Gateways, Financial Literacy, and Financial Statement Preparation Capability on MSMEs’ Financial Performance - Muhammad Yusra; Hermalia Syahfira; Sri Mulyati; Nur Afni Yunita (Jurnal Akuntansi dan Keuangan, 2026)
This study aims to examine the effect of payment gateway utilization, financial literacy, and the ability to prepare financial reports on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in North Aceh Regency. The population of this research consists of 17,309 MSMEs, and a sample of 99 respondents was selected using the Slovin formula and a stratified random sampling technique. Data were analyzed using outer model and inner model evaluation, followed by hypothesis testing. The results indicate that payment gateway utilization, financial literacy, and the ability to prepare financial reports have a positive and significant effect on MSME financial performance. These findings imply that strengthening digital financial adoption, improving financial literacy, and enhancing financial reporting capabilities can improve financial performance among MSMEs. Therefore, policymakers and related institutions are encouraged to design programs that support the integration of digital payments and the development of financial capacity for MSMEs.